The Determinants of gold price / Nur Izzati Syazwani Abdul Rahman - Abdul Rahman, Nur Izzati Syazwani (Faculty of Business Management, 2014)
Gold is the most popular investment of the precious metals. Gold is often used as a safe investment against currency, social, economic, or political crises. Throughout history, gold has been used as money, and everything else was measured in gold. This research therefore, was conducted in objective to determine the determinants of gold price. For this purpose, the researcher used secondary data, which is the data, are collected from Bloomberg and Bank Negara Malaysia Statistic. The factors that were selected in this study are called as independent variables. There are five independent variables which are inflation rate, interest rate, exchange rate, KLCI and crude palm oil (CPO) price. Therefore, the study is to examine the determinants that affect the fluctuation of gold price by using monthly data from January 2010 to September 2014. The multiple linear regressions are used in this study to assess the relationship between dependent variable (gold price) and the independent variables (inflation rate, interest rate, exchange rate, KLCI, and CPO price. The main findings suggest that the gold price is determined by these variables.